HUBUNGAN TINGKAT PENDIDIKAN DAN PENGETAHUAN IBU TENTANG TUMBUH KEMBANG ANAK DENGAN KUNJUNGAN IBU KE POSYANDU DI KABUPATEN SRAGEN - Ambarwati, Retno; Ratnasari, Nita Yunianti; Purwandari, Kristiana Puji (Akademi Keperawatan Giri Satria Husada Wonogiri, 2019)
Mother's education and knowledge about child development is one of the important factors in child development. Mother's education is good, so being able to receive all information from outside, especially on how to take good care of children and maintain good health of the child, a visit to the posyandu is also a very important factor for monitoring the growth and development of toddlers.The objective is to analyze the relationship between mother's education level and the level of mother's knowledge about the growth and development of children under five with the mother's visit to the posyandu at santa Anna Sragen kindergarten. This research is observational with cross sectional approach. Research subjects by 27 respondents. Sampling with a simple random sampling system. Data on mother's education, mother's knowledge, and mother's visit to the posyandu were obtained through questionnaires. Data analysis using Chi-Square test. The relationship between mother's education level with visits to the posyandu for mothers in Santa Anna Sragen Kindergarten with a ï£2count value of 6.217 (p= 0.013 <0.05) so that H0 was rejected and Ha was accepted. The relationship between the level of mother's knowledge about the growth and development of children under five with a visit to the posyandu in mothers in Santa Anna Sragen Kindergarten with a value of ï£2count was 10.919 (p= 0.004 <0.05) so that H0 was rejected and Ha was accepted. There is a positive and significant relationship between mother's education level with visits to posyandu for mothers in Santa Anna Sragen Kindergarten. There is a positive and significant relationship between mother's level of knowledge about the growth and development of children under five with visits to posyandu for mothers in Santa Anna Sragen Kindergarten.